Functional and Radiological comparison of tension band wiring versus screw fixation for the treatment of medial malleolar fractures - Dr. Phuritshabam Iboyaima Singh; Dr. Robium Naorem; Dr. Khwairakpam Devendra Singh (The Bioscan, 2026)
Background: Displaced medial malleolar fractures require stable internal fixation to restore ankle congruity and function. Both tension band wiring (TBW) and screw fixation (SF) are commonly used, but the optimal technique remains debated. This study aimed to compare the functional and radiological outcomes of TBW versus SF for these injuries. Methods: A prospective, randomized study was conducted at a tertiary orthopedic center. Fifty-two patients with acute, displaced medial malleolar fractures were randomized to undergo either TBW (n = 26) or SF (n = 26). Inclusion criteria were age 18–65 years and fracture displacement >2 mm. All patients were managed with standardized operative and rehabilitation protocols. Functional outcome was assessed using the Olerud–Molander Ankle Score (OMAS) at 6, 12, and 24 weeks postoperatively. Radiological union, time to union, and complications were also recorded. Results: Baseline characteristics were similar between groups. At 24 weeks, mean OMAS was 89.5 ± 8.1 in the TBW group and 87.2 ± 8.9 in the SF group (p = 0.28). Mean time to radiological union was 9.8 ± 2.0 weeks (TBW) versus 10.7 ± 2.1 weeks (SF) (p = 0.11). Complication rates, including infection, hardware irritation, and need for secondary procedures, were low and did not differ significantly between groups. Conclusion: Both tension band wiring and screw fixation provide satisfactory functional and radiological outcomes for displaced medial malleolar fractures, with comparable union times and complication rates. Implant choice should be individualized based on fracture characteristics and patient factors.